Pengaruh Risiko Kredit, Risiko Likuiditas, dan Permodalan terhadap Kinerja Keuangan - Pamungkas, Wihandaru Satya; Windyastuti, Septa (Universitas Muhammadiyah Metro, 2025)
This research aims to analyze the influence of credit risk (RK), liquidity risk (RL), and capital (MD) on financial performance (KK). The research sample is commercial banks listed on the Indonesia Stock Exchange (BEI) in 2018-2021. The sampling method used purposive sampling with conventional bank requirements, and a sample of 40 bank units was obtained and the number of observations used to test the hypothesis was 136 units. The data used is panel data. The analysis tool uses multiple linear regression based on the Hausman test using the random effect model (REM). The research results are that credit risk has a significant negative influence on financial performance, liquidity risk has a significant favorable influence on financial performance, and capital does not significantly influence financial performance.